Thryssatrema hanumantharaoi n. gen., n. sp. (Digenea: Fellodistomidae) from the longjaw thryssa, Thryssa setirostris (Clupeiformes: Engraulidae), of the Visakhapatnam coast, Bay of Bengal - Sailaja, B.; Madhavi, Rokkam (Zootaxa, 2012)
Thryssatrema hanumantharaoi n. sp., representing a new genus of fellodistomid digenean, is described from a clupeoidfish, the longjaw thryssa, Thryssa setirostris, collected from the coast of Visakhapatnam, Bay of Bengal. The new genusis characterized by possessing a combination of the following features: An elongate body; poorly developed suckers; twooval, symmetrical testes situated in the posterior half of the hindbody; a cirrus sac that extends posterior to the ventralsucker; a bipartite seminal vesicle; a median genital pore situated immediately anterior to the ventral sucker; a lobed,pretesticular ovary; uterine coils that fill the entire hindbody; small eggs, elliptical vitelline follicles forming two zonesanterolateral to the ovary; and a V-shaped excretory bladder. The new genus shows affinities to Prudhoeus and Elopsiumbut differs from the former in the body shape (elliptical versus oval), and by having poorly developed suckers, moreposteriorly located gonads and elliptical vitelline follicles arranged in two lateral zones in front of ovary. It differs fromElopsium mainly in the body shape (elliptical versus rounded) and distribution of vitelline follicles and in the V-shaped excretory bladder.